Psychosocial Stress and its Effect on Periodontal Tissues using Malondialdehyde as Oxidative Stress Biomarker - Mokashi, Anuradha; Abbayya, Keshava; Varma, Siddhartha; Zope, Sameer; Sugarimath, Girish; Pisal, Apurva (Journal of Nepalese Society of Periodontology and Oral Implantology, 2018)
Background: Stress is playing a major role as an aetiologic factor in the initiation of many systemic diseases. Similarly, it is also thought to be an aetiologic factor in the progression of periodontal diseases. Aim: The production of free radical species is associated with various inflammatory diseases and also during stressful conditions. Hence, an effort in the present study is done to correlate psychosocial stress and periodontitis using serum MDA as an oxidative stress biomarker. Materials and Methods: A current cross-sectional study included 201 individuals between 20 to 60 years of age. A periodontal examination included Probing Pocket Depth, CAL, Plaque Index, and Gingival Index. According to CAL individuals were divided into four groups i.e. healthy, slight (CAL = 1-2 mm), moderate (CAL = 3-4 mm) and severe (CAL = ≥5 mm) periodontitis. Psychosocial stress of the individuals was evaluated using occupational stress index. Serum MDA level was evaluated using spectrochromatometer. Results: Patients with stress demonstrated increased levels of MDA along with a higher loss of attachment. Conclusion: The results revealed statistically significant association between psychosocial stress and periodontitis indicating psychosocial stress as a risk factor for developing periodontitis.